2011
DOI: 10.1016/j.fct.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ROS, p53, p21 in DEHP- and MEHP-exposed LNCaP cells-protection by selenium compounds

Abstract: Keywords: DEHP MEHP p53 p21 ROS Selenium a b s t r a c t This study was designed to investigate the hypothesis that the toxic effects of di(2-ethylhexyl)phthalate (DEHP), the most abundantly used plasticizer and ubiquitous environmental contaminant that cause alterations in endocrine and spermatogenic functions in animals is mediated through the induction of reactive oxygen species (ROS) and activation of nuclear p53 and p21 proteins in LNCaP human prostate adenocarcinoma cell line. Protective effects of two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 58 publications
2
21
0
2
Order By: Relevance
“…Increased ROS generation with MEHP exposure in MA-10 Leydig cells has been inhibited by N-acetylcysteine (Fan et al 2010). Moreover, in the above-mentioned in vitro studies (Erkekoglu et al 2010a(Erkekoglu et al , 2011b, we demonstrated that Se supplementation was highly protective against ROS production, p53-inducing potential, cellular antioxidant status-modifying effect, as well as cytotoxicity and genotoxicity induced by DEHP and MEHP in both MA-10 Leydig and LNCaP cells, stressing the role of Se as an effective cellular redox regulator. Thus, the results of the present study are supported by our previous in vitro findings and the data of the above-mentioned in vivo study (Erkekoglu et al 2011a) regarding the critical role of Se in the modulation of redox status in the testicular cells and its protective role in DEHP-induced toxicity on Sertoli cells.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Increased ROS generation with MEHP exposure in MA-10 Leydig cells has been inhibited by N-acetylcysteine (Fan et al 2010). Moreover, in the above-mentioned in vitro studies (Erkekoglu et al 2010a(Erkekoglu et al , 2011b, we demonstrated that Se supplementation was highly protective against ROS production, p53-inducing potential, cellular antioxidant status-modifying effect, as well as cytotoxicity and genotoxicity induced by DEHP and MEHP in both MA-10 Leydig and LNCaP cells, stressing the role of Se as an effective cellular redox regulator. Thus, the results of the present study are supported by our previous in vitro findings and the data of the above-mentioned in vivo study (Erkekoglu et al 2011a) regarding the critical role of Se in the modulation of redox status in the testicular cells and its protective role in DEHP-induced toxicity on Sertoli cells.…”
Section: Discussionmentioning
confidence: 96%
“…Several mechanisms have been proposed for the testicular toxicity of DEHP, and recent evidence supports the view that oxidative stress is one of the underlying mechanisms (Erkekoglu et al 2010a(Erkekoglu et al , b, 2011bFan et al 2010). Oxidative stress is the imbalance between formation of reactive oxygen species (ROS) and antioxidant defense mechanisms.…”
mentioning
confidence: 94%
“…Evidence of phthalate transfer to the EMB and fetus has been evident through detection of MEHP in meconium, amniotic fluid, cord blood, rodent fetal tissues, and placental perfusate [2028]. It has been previously demonstrated that MEHP can induce general oxidative stress and inflammation in various reproductive tissues and developmental tissues via the increased generation of ROS, though these studies were conducted in other model organisms and at different stages of development [12, 13, 29, 30]. It has been demonstrated that several chemical compounds have the ability to modify the embryonic redox environment, and that these changes can result in teratogenic outcomes [5, 3135].…”
Section: Introductionmentioning
confidence: 99%
“…57 Son 30 yılda ise DEHP'nin hücre içi ROS düzeylerini artırdığına dair birçok veri elde edilmiştir. [58][59][60][61][62][63] Yaptığımız çalışmalarda, sıçanlara 10 gün süreyle DEHP uygulamasının karaciğer, böb-rek ve testiste anlamlı düzeyde lipit peroksidasyon artışına neden olduğu belirlenmiştir. Testiste okside GSH düzeylerinde önemli artış ve total ve indirgenmiş GSH düzeylerinde gözlenen azalmalar nedeni ile, DEHP'nin önemli düzeyde oksidatif strese neden olduğu gözlenmiştir.…”
Section: R Re Ea Ak Kt Ti If F Ounclassified